Does income imply food security in coffee growing communities? A case study in Yayu, Southwestern Ethiopia - Jemal, Omarsherif M.; Callo-Concha, Daniel; van Noordwijk, Meine (Frontiers in Sustainable Food Systems, 2022)
The impacts on food security of a transition from agriculture focused on local consumption to the participation in global markets are uncertain, with both positive and negative effects reported in the literature. In Ethiopia, coffee production for global markets has attracted growers from across the country to the coffee-forest zones. From a national perspective, the area is not a priority for food security enhancement, as financial indicators suggest food sufficiency. In this setting, we collected food security and dietary intake data from a total of 420 (3X140) units of households, non-breast-feeding children under 5 years, and women of reproductive age. Sampling was done in two-stages, a random selection of 300 households (out of a total of 4,300) Yayu, followed by sub-sampling of households with a child and woman meeting the above-mentioned criteria. Samples were used to determine a number of food and nutrition security indicators. More than 83% of the households were found to be hunger-free in the shortage season, but dietary diversity was suboptimal. More than 50% of children under 5 years of age and women lacked foods containing heme iron in the surplus season and 88% in the shortage season. Household food security during the surplus season did not depend on income, but wealth was significantly correlated (p < 0.01) with all of the food insecurity indicators except the “Body Mass Index” of target women in the shortage season. The strongest and weakest correlation was with the “House Food Insecurity Access Scale” (−0.85), and “Weight-to-Age Z-Score” (0.25), respectively. Overall, Yayu is not fully food secure, though the situation is better than average for the country. While household income helps in achieving calorific sufficiency, greater awareness of the relevance of dietary diversity and the local means to achieve it is needed to further improve nutritional status, regardless of the participation in global markets.